CMOS Circuits for Biological Sensing and Processing - Mitra, Srinjoy; Cumming, David R. S. (Springer International Publishing : Imprint: Springer, 2018)
This book provides the most comprehensive and consistent survey of the field of IC design for Biological Sensing and Processing.  The authors describe a multitude of applications that require custom CMOS IC design and highlight the techniques in analog and mixed-signal circuit design that potentially can cross boundaries and benefit the very wide community of bio-medical engineers. Provides a single-source reference to the state-of-the-art in analog and mixed-signal circuit design for biological and chemical sensing; Highlights numerous applications, categorized as Ex-vivo, In-vivo, and Wearable and Technology Trends; Explains basic details of the circuits used in a very consistent manner, identifying clearly the CMOS and non-CMOS technologies used, along with the method to interact with the transducer (various kinds of electrodes, ion-sensitive layers, Carbon nanotubes etc.).